Studies in East European Jewish mysticism and Hasidism - Weiss, J. G. (Joseph George), 1918-1969 (The Littman Library of Jewish Civilization, 2013)
Joseph Weiss (1933-69) was committed to identifying and describing the mystical element in Hasidism and to unravelling the spiritual and historical meaning of the Hasidic movement. The studies in this volume, most of them written more than 40 years ago, are still quoted in every serious study of Hasidism. The introduction by Joseph Dan examines Weiss's scholarship in the context of subsequent academic research and in the resurgence of Hasidism since World War II. He concludes that many of Weiss's studies are as relevant to understanding developments in the contemporary Hasidic world as they are for understanding the emergence and growth of Hasidism in the eighteenth century.